Quality Control Measures as Predictors of Quality University Education in Nigeria - Akinwumi , Femi Sunday; Oyekan , Opeyemi Aderonke (West African Journal of Open and Flexible Learning, 2026)
Education is the leading factor out of the potential of the individuals in society and the acquisition of skills, aptitudes and competencies necessary for self-realisation and coping with life’s challenges. University education is seen to be the largest repositories of certified knowledge for the improvement, advancement and development of society and the nation as a whole. Enhancing quality in university education therefore must be based on developing educational systems that are integrated and responsive to the obstacles of academic achievement. The eight quality control measures when combined, have a positive multiple correlation with the quality of graduates (R=0.34). Furthermore, 33.9% of the total variation in the quality of graduates is accounted for by the 8 quality control measures. The benefit and impact of quality education also make invaluable contributions to all areas of human development and helping to eradicate poverty. Recommendations are also made to enhance the quality of university education because of its strategic position in the educational system.